a-7a+3=6a+3

Simple and best practice solution for a-7a+3=6a+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a-7a+3=6a+3 equation:


Simplifying
a + -7a + 3 = 6a + 3

Reorder the terms:
3 + a + -7a = 6a + 3

Combine like terms: a + -7a = -6a
3 + -6a = 6a + 3

Reorder the terms:
3 + -6a = 3 + 6a

Add '-3' to each side of the equation.
3 + -3 + -6a = 3 + -3 + 6a

Combine like terms: 3 + -3 = 0
0 + -6a = 3 + -3 + 6a
-6a = 3 + -3 + 6a

Combine like terms: 3 + -3 = 0
-6a = 0 + 6a
-6a = 6a

Solving
-6a = 6a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6a' to each side of the equation.
-6a + -6a = 6a + -6a

Combine like terms: -6a + -6a = -12a
-12a = 6a + -6a

Combine like terms: 6a + -6a = 0
-12a = 0

Divide each side by '-12'.
a = 0

Simplifying
a = 0

See similar equations:

| 1+3n+6=-5 | | (3+3i)+(2+4i)= | | -7w(w-2)=5(3-w) | | 2a^2+5a+18=0 | | 4(u+1)=20 | | x+5-5x=13 | | 5x-23=5x-1 | | 2x^3+5x^2-x-6=0 | | -8x+2=-6 | | 3=x+5-4 | | y+-6x+-9=0 | | (3x^3-24)=0 | | 4(3+5w)=11 | | ln(x^2+3x+4)=0 | | -15+2(x)=-11 | | -15+2(5)= | | -2a+3-4=-1 | | -15+2(3)= | | x-3-1=2 | | 3m+2x=y | | 4 = b8 | | 4t+1=7t+10 | | 17-6x+4=3x+21-3x | | -13+12(x)=11 | | -8+14v=12v | | n+31+2n=17 | | 0=r-4+6 | | 13=u-6 | | -13+12(7)= | | 2(b+3)=14 | | 5p=-8+6p | | 18s-11s-5s=20 |

Equations solver categories